Premalignant and malignant lesions in endometrial polyps in patients undergoing hysteroscopic polypectomy - Lenci,Marco Antonio (2014)
Objective : To evaluate the incidence of premalignant lesions and cancer in endometrial polyps, in patients undergoing hysteroscopic polypectomy. Methods : The results of 1,020 pathological examinations of patients submitted to hysteroscopic polypectomy were analyzed, as well as their diagnostic and surgical hysteroscopy findings. As to their menstrual status, 295 (28.9%) patients were in menacme. Of the total, 193 (65.4%) presented abnormal uterine bleeding, and 102 (34.6%) were asymptomatic with altered endometrial echo on transvaginal ultrasound. Out of 725 (71.1%) postmenopausal patients, 171 (23.6%) were symptomatic (abnormal uterine bleeding), and 554 (76.4%) were asymptomatic with endometrial echo >5.0mm. Results : Twenty-one (2.0%) patients presented premalignant lesions in the polyps, 13 had simple glandular hyperplasia, of which 5 had no atypia, and eight presented atypia. Eight polyps presented focal area of complex hyperplasia: 4 with atypia and 4 without lesions. Cancer was diagnosed in 5 (0.5%) polyps. Of the 21 polyps that harbored premalignant lesions, 12 were interpreted as benign in diagnostic and surgical hysteroscopy. Of the polyps with cancer, 4 were also histeroscopically interpreted as normal. Conclusion : Symptomatic polyps in menacme and in all postmenopausal women should be resected and submitted to histopathological examination, since they may have a benign aspect, even when harboring areas of cellular atypia or cancer.